Roles of intralesional bacteria in the initiation and progression of oral squamous cell carcinoma - Zhuoyan Luo; Shiping Lv; Fangzhi Lou; Li Yan; Jingyi Xu; Ning Kang; Yunmei Dong; Xin Jin (Cancer Medicine)
Abstract Background Oral squamous cell carcinoma (OSCC) is the predominant form of head and neck cancer, often diagnosed at late stages, resulting in a poor prognosis. Recent studies indicate a potential association between OSCC and microbial presence. Microorganisms have been identified in various tumors and lesions, including OSCC and oral potentially malignant disorders (OPMDs). Intralesional microbiota are considered important components of the tumor microenvironment (TME) and may contribute to carcinogenesis. Methods Sources were collected through thorough searches of databases PubMed and Embase. The review focused on microbial characteristics, potential origins, and their impact on cancer progression. Results Bacteria display varying abundance and diversity throughout the stages of OSCC and OPMDs. Intraleisional bacteria may have diverse sources, including not only oral plaque and saliva but also potentially the gut. Intralesional bacteria have both pro‐carcinogenic and anti‐carcinogenic effects, affecting processes like cell proliferation, invasion, and immune response. Conclusions Intralesional microbiota are crucial in OSCC and OPMDs, influencing both disease progression and treatments. Despite their significance, challenges like inconsistent sampling and microbial identification remain. Future research is required to fully understand their role and improve clinical applications.